Performance now: live art for 21st century (Thames & Hudson, 2016)
Now one of the most highly visible art forms, in the last two decades performance has emerged from the margins to become an essential vehicle for communication, transforming museums and galleries into lively cultural hubs for future generations. This landmark survey by renowned authority RoseLee Goldberg reveals how live art has developed in the 21st century as a visual medium, a global language and a political force. A mesmerizing survey of this most varied art form, Performance Now is the ultimate reference for artists, art students and historians, as well as theatre, film, dance and architecture enthusiasts with an eye on the avant-garde.
English
Keywords: N5300-7418 Visual Arts- History; Performance Art